Strand Corrosion in Prestressed Concrete Structures - Wang, Lei (Springer Nature Singapore : Imprint: Springer, 2023)
This is an open access book. This book focuses on the durability problems of existing prestressed concrete (PC) structures caused by strand corrosion, clarifies the mechanical behavior of corroded prestressing strands, corrosion-induced cracking, bond degradation, prestress loss and structural performance deterioration of PC structures, and proposes the corresponding prediction models. We hope that this text may be useful for those who work in the field of civil and construction engineering, as well as for those involved in the area of maintenance and management of prestressed concrete structures. Its aim is to provide the knowledge, tools, and methods to understand the deterioration phenomena of prestressed concrete structures. It is suitable for teachers and students majoring in civil engineering in universities, and researchers in the field of civil engineering. It is also suitable for practitioners of design institutes, construction units, supervising units and traffic management departments. This book is also applicable to anyone else who wants to understand the corrosion of strand. Enthusiasts of civil engineering are also a potential audience. At the same time, this book can also stimulate the interest of young scholars in interdisciplinary research.